A controlled crossover study to assess the role of dietary eliminations in reducing the severity of atopic dermatitis in children - Pretty Mathew; Rajiv Sridharan; Thyvalappil Anoop; Ajayakumar Sreenivasan (Wolters Kluwer Medknow Publications, 2019)
Background: In the pathogenesis of atopic dermatitis (AD), immune sensitization to food-derived allergens has a role. However, the evidence of allergen sensitization is not a proof of clinically relevant allergy and it has to be confirmed by food challenges so that unnecessary food restrictions in growing children can be avoided. Aims and Objectives: This study was conducted to assess the clinical severity of AD in children after certain dietary modifications and to correlate absolute eosinophil count (AEC) with dietary modification. Materials and Methods: A total of thirty AD children were enrolled randomly into a trial period of egg and cow's milk exclusion diet or control period of egg and cow's milk inclusion diet of 3 weeks. At the end of 3 weeks, patients resumed their normal diet to minimize any carryover effect for next 3 weeks. In the last 3 weeks, the trial and the control groups were crossed over. Patients were assessed at baseline and at the end of each 3-week period using SCORing AD (SCORAD) index and AEC. The data were analyzed using paired t-test. Results: The mean SCORAD at the end of control and trial period was 18.3 and 14.3, respectively, with a mean difference of 3.4, which is statistically not significant (P = 0.165). The mean AEC at the end of control and trial period was 836.5 and 799.6, respectively, the reduction being statistically not significant. Conclusion: Our study could not confirm the beneficial effects of an allergen avoidance diet in AD. We propose that dietary elimination advices should be given only to patients with a definite history of food-induced exacerbations of the disease.